Effect of Adding Orange Sweet Potato Puree (Ipomoea Batatas Linneaus) on the Physical and Sensory Properties of Steamed Bakpia - Raihanah, Rana; Rusilanti, Rusilanti; Yulianti, Yeni (Sahabat Publikasi, 2025)
This study was conducted to analyze the effect of adding orange sweet potato puree with a percentage of 25%, 50%, and 75% in making steamed bakpia on physical properties and sensory quality. The method used in this study was an experimental method with three types of different treatments: steamed bakpia with the addition of 25% puree, 50% puree, and 75% puree. Organoleptic validation tests conducted on five lecturers of the Culinary Arts Education Study Program, Jakarta State University showed that the addition of orange sweet potato puree of 25%, 50%, and 75% was feasible for use in research. Physical quality tests were carried out by measurement, calculation through equations, and Anova tests on the aspects of expansion and stability. The results of the physical quality test showed that there was an effect of the addition of orange sweet potato puree on the stability of the steamed bakpia's expansion power with the results of steamed bakpia with the addition of puree of 50% and 75% being significantly different, while in the expansion power aspect of steamed bakpia there was no effect of the addition of orange sweet potato puree. The results of the Duncan test showed that steamed bakpia with the addition of 75% orange sweet potato puree was the best in terms of stability. The sensory quality test was carried out using the Kruskal-Wallis test with data collection through a hedonic quality test on 45 semi-trained panelists with the results that there was no effect of the addition of 25%, 50%, and 75% orange sweet potato puree on making steamed bakpia in all aspects except for the sponge cake color aspect. The results of the Tuckey's test showed that steamed bakpia with the addition of 75% orange sweet potato puree was the best in terms of sponge cake color. Based on the results of this study, the recommended product is steamed bakpia with the addition of 75% orange sweet potato puree.